Thermal-shock stable Al2O3 crucible for superalloy smelting through slip casting with particle gradation. Issue 6 (15th March 2023) - Fan, Jiaxian; Fan, Hongna; Song, Zhuo; Guo, Yajie; Li, Minmin; Li, Xin; Qi, Changjian; Xu, Xiqing
Abstract: Crucible is a key vessel in superalloy smelting, and high-performance crucible is quite important to the development of superalloy. Pointed at the easy cracking and poor thermal-shock stability of Al2 O3 crucibles for superalloy smelting, particle gradation was managed in slip casting of Al2 O3 crucibles. The ceramic slurry in good dispersion was prepared by optimizing particle gradation, with solid content of 86 wt% and viscosity of lower than 0.5 Pa s. For the crucible with optimized particle gradation, the density was 2.37 g/cm 3, the linear shrinkage was less than 2%, the porosity was 18.72%, the bending strength was close to 22 MPa and the thermal expansivity was 2.77 × 10 −6 /°C. Strength retention rate was raised to evaluate the thermal shock stability of crucibles, which was up to 73.5% after five-time thermal shock, well meeting the requirements of crucibles for superalloy smelting, and the superior thermal-shock stability was attributed to the uniform network microstructure and low thermal expansivity. The optimal particle gradation in experiments was explained in terms of Dinger-Funk model. This work provides a reference for preparing high-performance Al2 O3 crucibles for superalloy smelting with low thermal expansivity as well as excellent thermal-shock stability.